Influence of reduced graphene oxide on flow behaviour, glass transition temperature and secondary crystallinity of plasticized poly(vinyl chloride). Issue 49 (7th August 2020) - Akhina, H.; Ramya, Koduvayur A.; Gopinathan Nair, M. R.; Saiter-Fourcin, Allisson; Garda, Marie-Rose; Deshpande, Abhijit P.; Kalarikkal, Nandakumar; Thomas, Sabu
Abstract : Understanding the rheological behaviour of thermoplastic nanocomposites is important to obtain a concrete knowledge of their processability. Abstract : Understanding the rheological behaviour of thermoplastic nanocomposites is important to obtain a concrete knowledge of their processability. The viscoelastic properties of nanocomposites are a reflection of their morphology. The study of flow and deformation of nanocomposites provides essential information related to prevalent interactions in the system as well as contribution from the dispersion of incorporated nanofillers. In the present study, plasticized polyvinyl chloride/reduced graphene oxide nanocomposites (PPVC/RGO) were fabricated using melt mixing technique with different filler concentration. Flow behaviour of the nanocomposites was analyzed using small amplitude oscillatory shear (SAOS) measurements and it indicated an enhancement in the storage modulus ( G ′), loss modulus ( G ′′) and complex viscosity ( η *) with RGO content. This can be attributed to very good dispersion and reinforcing effect of RGO in PPVC matrix as supported by TEM and FTIR results. Weak gel model is used to fit the rheological parameters and is found to be in excellent agreement with the SAOS experiments. Thermal history of the prepared nanocomposites was learned using differential scanning calorimetry. A shift in glass transition temperature ( T g ) to higher temperature region could be seen, that manifest the effect of RGO in the amorphous portion of PPVC. An interesting property called secondary crystallinity was also found in these materials.